The World Crisis and Its Impact on Regional Development - Štěpánek, Zdeněk (Światowy kryzys i jego wpływ na rozwój regionalny, 2010)
The financial crisis, which started in autumn 2008 and spread all over the world, has inflicted qualitative as well as quantitative restrains in the regional development. The paper deals with some implications of the crisis in case of the Czech Republic. The regional politics has been recently weakened due to the lack of finances. In such a situation the attentionof the ruling is focuses on the distribution channels of EU funds.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 110, s. 119-124